Billionaires are so Predictable - Blair Fix (Economics from the Top Down, 2023)
Have you ever wondered what it takes to become a billionaire? Do you need rare genius? Exceptional acumen? Miraculous foresight? An uncompromising work ethic? On all four counts, the answer is no. It turns out that to become a billionaire, what you really need is the right social setting. You need to live in a society that is suitably rich and appropriately unequal. Without those things, your chances of wearing the billionaire badge are low. In this post, I'll do the math. Using data from Forbes, I'll show you how the billionaire headcount varies across countries. Then I'll show you how to predict this variation. Forget about character traits and personal histories. We don't need them. To predict how many billionaires a country has, we can get surprisingly far just by knowing the distribution of income.
Keywords: P; P1; D3; G3; G32; 330; billionaires; corporation; distribution; ownership